The Xerias Window near Argos (Peloponnesus) - an example of a regional geological structure of interregional importance - Kunz, Erwin (Bulletin of the Geological Society of Greece, 2024)
The Argolic-Arcadian border range is built up by rocks of the Tripolitza and the Pindos Zones. Its tectonic architecture is deeply exposed in the area of the Xerias Window. Key structures are worked out in this article. The nappe-shaped superposition of the Tripolitza Zone by the Pindos Zone is obvious in the frame of the Xerias Window. The vergence of the key structures of the latter varies everywhere between W and SW, which proves a relative transport of the Pindos Zone as a whole in that direction. After finishing the nappe transport both Pindos and Tripolitza Zone experienced further, collective deformations, which are brought in a probable chronological order. Round about since Upper Miocene, the compressive stress of the Hellenides was followed by young extensional tectonics, which continues until today. Its influence on the development of the window and on the forming of its frame is described. The most important faults that can be related to the spreading tectonics are called within this investigation as Xerias Faults. Finally, the impacts of the strong regressive erosion, of the numerous landslides, and of the widespread slope waste both on exposing and on covering the tectonic elements are regarded.